The research on the application of artificial intelligence in visual artbased on souvenir design - Qiu, Liping; Rahman, Ahmad Rizal Abdul; Dolah, Mohd Shahrizal Bin; Ge, Shengguo (World Scientific and Engineering Academy and Society, 2024)
This paper will introduce the application of artificial intelligence (AI), machine learning, and deep learning in art design and visual arts, and how these technologies can be used to create unique souvenirs. In the field of art design, AI and machine learning can be used to automatically generate artwork and patterns, providing more inspiration and creativity, and can also help artists better understand their audience and market. The application of deep learning in the field of visual arts includes image recognition, image classification, image generation, and so on. In the field of souvenir design, the use of AI and machine learning can help designers better understand market needs and consumer trends to create unique souvenirs. Taken together, the application of AI, machine learning, and deep learning technologies has great potential and creativity in the fields of art design and souvenirs.